Evaluación de la actividad física en pacientes con enfermedad pulmonar obstructiva crónica - Torres-Castro,Rodrigo (Sociedad Médica de Santiago, 2017)
The prevalence and mortality of chronic obstructive pulmonary disease (COPD) is increasing in Chile, constituting a public health problem. Pulmonary and systemic consequences of COPD affect physical activity, as the disease progresses. There are multiple means for physical activity assessment, from low cost and easily applicable questionnaires to sophisticated laboratory tests. Physical inactivity is a modifiable risk factor for morbidity and mortality in patients with COPD. Physical activity interventions not only contribute to decrease the likelihood of mortality, but also protect from comorbidities, especially cardiovascular ones. It also plays a major role avoiding functional limitations of these subjects. Dyspnea and fatigue render exercise as an unpleasant activity for most patients with COPD. If psychological alterations such as anxiety and depression are summed, these patients drift towards an inactive lifestyle. This article analyzes several tools available to assess physical activity is patients with COPD, useful in clinical practice.